Curricular training report as a clinical research coordinator in Blueclinical Ltd - Valente, Vanessa Sofia Silva (2018)
This report describes the activities developed within the curricular internship as a clinical research coordinator in the Clinical Research Partnership business area of Blueclinical. The internship lasted 10 months – from July 2014 until April 2015. This report provides a general view of the implementation of clinical trials and observational studies in clinical research centers alongside with my experience during the 10 months of curricular internship as a clinical research coordinator in Centro Hospitalar de Vila Nova de Gaia/Espinho. To understand the regulations under which my activities were developed, clinical research is contextualized in what regards it’s legal and ethical framework and the evolution of the number of clinical trials in Portugal along the last years. In the overall result, I have experienced a great improvement in understanding the coordination of clinical trials and observational studies, as well as the improvement of my soft skills.